2018
DOI: 10.1245/s10434-018-6549-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Mechanism of Acellular Dermal Matrix on Capsule Formation in Expander–Implant Breast Reconstruction After Postmastectomy Radiotherapy

Abstract: Use of ADM reduced myofibroblasts, vascularity, fibroblasts, and EndoMT in capsule tissues. Moreover, ADM use decreased macrophages, a key regulator of tissue fibrosis, as well as TGF-β1 and PDGF-B expression. We hope that these results provide basic concepts important for prevention of capsular contracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 35 publications
0
45
1
2
Order By: Relevance
“…Notably, capsular contracture, which was the main complication of previous subcutaneous breast reconstruction procedures, has been reduced with the use of ADMs. Kim et al reported that the levels of myofibroblasts were significantly lower in ADM capsules than in submuscular capsules [11]. Now, with advances in oncology such as the skin-sparing mastectomy with optimal skin flap, improved implants, and ADMs, prepectoral breast reconstruction has become feasible.…”
Section: Historymentioning
confidence: 99%
“…Notably, capsular contracture, which was the main complication of previous subcutaneous breast reconstruction procedures, has been reduced with the use of ADMs. Kim et al reported that the levels of myofibroblasts were significantly lower in ADM capsules than in submuscular capsules [11]. Now, with advances in oncology such as the skin-sparing mastectomy with optimal skin flap, improved implants, and ADMs, prepectoral breast reconstruction has become feasible.…”
Section: Historymentioning
confidence: 99%
“…In this study, there was no significant difference between the thickness of nonirradiated and irradiated ADM capsules. 2 Myofibroblasts and macrophages, which play central roles in tissue fibrosis, were significantly reduced in the ADM capsules compared with the subpectoral capsules. We first investigated the number of endothelial-mesenchymal transition (EndoMT) cells and vimentin positive fibroblasts, and the TGF-b1 and PDGF-B transcript levels in the capsular tissues.…”
Section: Presentmentioning
confidence: 89%
“…As it functioned as a barrier between the mastectomy skin and the implant, ADM has made it possible to return to PBR. Kim et al reported that the levels of myofibroblasts were significantly lower in ADM capsules than in submuscular capsules [ 23 ]. With advances in oncologic surgical technique such as the NSM with optimal skin flap, improved implants, and ADMs, prepectoral breast reconstruction has become feasible.…”
Section: Discussionmentioning
confidence: 99%